2020
DOI: 10.5535/arm.2020.44.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Effect of Daily Rehabilitation Time on Functional Gain in Stroke Patients

Abstract: Objective To demonstrate the effect of daily treatment time on recovery of functional outcomes and how each type of rehabilitation treatment influences the improvement of subgroups of functional outcomes in stroke patients.Methods We conducted a retrospective study in 168 patients who were admitted to the Department of Rehabilitation Medicine between 2015 and 2016. Patients who experienced their first-ever stroke and unilateral lesions were included. All patients underwent conventional rehabilitation treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…These results imply that there is a relationship between physical intervention or amount of physical activity during hospitalization and the risk of HAD. In addition, ADRT seems to correlate positively with improved physical function and ADL after stroke [ 28 ]. Yosef-Brauner et al examined the effect of the number of physical therapy (PT) sessions on muscle strength and physical function and showed that PT twice a day was better than once a day to facilitate the recovery process in patients who suffer from intensive care unit-acquired weakness [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results imply that there is a relationship between physical intervention or amount of physical activity during hospitalization and the risk of HAD. In addition, ADRT seems to correlate positively with improved physical function and ADL after stroke [ 28 ]. Yosef-Brauner et al examined the effect of the number of physical therapy (PT) sessions on muscle strength and physical function and showed that PT twice a day was better than once a day to facilitate the recovery process in patients who suffer from intensive care unit-acquired weakness [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of exercise preference in stroke survivors are classified into the three categories: (i) patient-related, (ii) rehabilitation provider–related, and (iii) rehabilitation service system–related ( 3 , 34 , 35 ). Patient-related consequences include improved adherence to rehabilitation ( 9 , 13 , 15 ), enhanced the level of physical activity ( 9 , 14 ), promoted motor recovery and quality of life of individuals with stroke ( 9 , 36 , 37 ). Rehabilitation provider–related consequences include providing a personalized regimen ( 9 , 14 , 21 , 26 ), job satisfaction ( 26 ), professional identify ( 27 ), and communication promoting in patients and rehabilitation team ( 26 , 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important to determine the factors such as age and LOS that correlate with balance performance and motor function after stroke to develop a comprehensive rehabilitation that maximizes functional independence. Early post-stroke rehabilitation could enhance balance performance and functional motor outcomes in poststroke individuals (14). Thus, this study will examine the effect of an intensive inpatient rehabilitation programme on balance performance and motor function and determine whether age and length of stay are associated with balance performance and motor function outcomes in post-stroke individuals.…”
Section: Introductionmentioning
confidence: 99%